SCIENTIFIC AND METHODOLOGICAL DETERMINANTS OF TAX POLICY IN THE CONDITIONS OF THE NATIONAL ECONOMY TRANSFORMATION (World of finance, 2022)
Introduction. The formation of financial resources of the state and united territorial communities in the conditions of transparency of fiscal relations requires the authorities to implement adequate to European standards tax policy. The relevance of the study of comprehensive aspects of tax policy of the state is due to the implementation of effective approaches in the direction of financial support of priority sectors of Ukraine's economy. Today, the leading role belongs to tax payments, which under conditions of rational administration should become a catalyst for innovative development of Ukraine. It is with the help of tax policy tools that it is possible to create favorable conditions for doing business, investing, innovating and improving the well-being of citizens. Therefore, the priority is to study modern aspects of tax policy of Ukraine in order to form ways to improve its efficiency.The purpose of the article is to substantiate the peculiarities of the formation and effective implementation of the tax policy of the state at the present stage of socio-economic development of Ukraine.Results. The essential determinants of taxes and tax policy in the context of their impact on the development of the state economy are identified. The basic principles of tax policy formation in Ukraine are considered. The functions of tax policy were monitored, among which considerable attention was paid to the fiscal function as a priority and dominant in modern inter-budgetary processes. The article highlights the features of tax policy in terms of shifting the tax burden from mobile factors of production to natural resources. Emphasis is placed on cooperation between the state, taxpayers and the public in the direction of developing effective measures to reform the tax system through the use of incentives, digital technologies, social orientation of taxation. The analysis of the main parameters of fiscal efficiency of the tax policy of the state is carried out, as a result of which the important role of tax payments in financial resources of the state and local governments is confirmed. The factors that have a negative impact on taxation processes in the state are highlighted. Guidelines for improving the tax policy of Ukraine in the conditions of transformation of the national economy are offered.Perspectives. In further research, attention will be paid to current aspects of digitalization of the tax space of the state and the implementation in the Ukrainian system effective practices of innovation of taxation processes of foreign countries.